1975
DOI: 10.1002/ar.1091810408
|View full text |Cite
|
Sign up to set email alerts
|

A simple, single‐injection method for inducing long‐term paralysis in embryonic chicks, and preliminary observations on growth of the tibia

Abstract: A method for inducing paralysis in embryonic chicks is described. This involves single injections of the neuromuscular blocking agents, D-tubocurrarine Chloride or decamethonium iodide, into 10-day embryos. The dose which optimises survival and paralysis is determined along with the effect of the drugs on embryonic growth. Decamethonium iodide at a dose of 1 mg per embryo gave maximum survival and paralysis to 18 days of incubation. Paralysis was assessed by observation of treated embryos in ovo and by examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…This trend is particularly evident in the autopodial segments, as was reported by Pitsillides (2006) for chick embryos treated with DMB and pancuronium bromide. The correlation of reduced size with immobilization has been frequently reported (Sullivan, 1966;Murray and Drachman, 1969;Hall, 1975;Hall and Herring, 1990;Kim et al, 2009). Sohn and Kim (2007) found that the denervated limbs of the pipid frog Hymenochirus were slightly shorter than the contralateral, nondenervated limbs in the same individual.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This trend is particularly evident in the autopodial segments, as was reported by Pitsillides (2006) for chick embryos treated with DMB and pancuronium bromide. The correlation of reduced size with immobilization has been frequently reported (Sullivan, 1966;Murray and Drachman, 1969;Hall, 1975;Hall and Herring, 1990;Kim et al, 2009). Sohn and Kim (2007) found that the denervated limbs of the pipid frog Hymenochirus were slightly shorter than the contralateral, nondenervated limbs in the same individual.…”
Section: Discussionmentioning
confidence: 77%
“…The four main effects that are observed in tadpoles can be recognized in amniotes such as birds (chick embryos: Sullivan, 1966;Murray and Drachman, 1969;Hall, 1975;Hall and Herring, 1990;Quin et al, 1998;Pitsillides, 2006), and mammals (rat embryos: Quinn et al, 1998;Coutinho et al, 2002;Kahn, 2009). Based on these data (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case for the dependence of chick motor development on practice effects and movement can be made at embryonic stages. Considerable evidence indicates that the spontaneous embryonic motility of the chick influences muscle differentiation (Drachman, 1968), prevents the atrophy of already differentiated muscle (Jacobson, 1978), plays an important role in the development of joints (Drachman & Sokoloff, 1966;Hall, 1975;Murray & Drachman, 1969), and regulates the natural cell death of spinal motoneurons (Pittman & Oppenheim, 1978. The immobiliiation of the embryo for as little as 2 days by means of pharmacological agents can lead t o long-lasting and perhaps permanent muscle and joint abnormalities (Oppenheim, Pittman, Gray, & Maderdrut, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that alterations in the correct movement of limbs can produce severe malformations during the ontogeny, including adult pathologies (Hosseini & Hogg, 1991; Arokoski et al, 2000; Pitsillides, 2006; Nowlan et al, 2010, 2012; Nowlan, Chandaria & Sharpe, 2014; Abdala & Ponssa, 2012; Kim et al, 2015; Ponssa & Abdala, 2016; Verbruggen et al, 2016; Ford et al, 2017). The absence or reduction of movement in early stages of development produce similar phenotypical alterations both in free-living organisms, such as anurans (Abdala & Ponssa, 2012), or in organisms living in “controlled” environments, such as mice (Coutinho et al, 2002; Kahn et al, 2009) or chicken (Sullivan, 1966; Murray & Drachman, 1969; Hall, 1975; Hall & Herring, 1990; Quinn et al, 1998; Pitsillides, 2006). Likewise, joint-tissues that are subject to extreme mechanical loads caused by overuse can suffers similar consequences (Shwartz, Blitz & Zelzer, 2013) as was studied in bones and articular cartilage (Shwartz, Blitz & Zelzer, 2013) tendons (Sharma & Maffulli, 2005; Maeda et al, 2011), and menisci (Adirim & Cheng, 2003).…”
Section: Introductionmentioning
confidence: 99%